Histone Deacetylase 9 Activates IKK to Regulate Atherosclerotic Plaque Vulnerability. Issue 6 (28th August 2020) - Asare, Yaw; Campbell-James, Thomas A.; Bokov, Yury; Yu, Lydia Luya; Prestel, Matthias; El Bounkari, Omar; Roth, Stefan; Megens, Remco T.A.; Straub, Tobias; Thomas, Kyra; Yan, Guangyao; Schneider, Melanie; et al.
Abstract : Rationale: Arterial inflammation manifested as atherosclerosis is the leading cause of mortality worldwide. Genome-wide association studies have identified a prominent role of HDAC (histone deacetylase)-9 in atherosclerosis and its clinical complications including stroke and myocardial infarction. Objective: To determine the mechanisms linking HDAC9 to these vascular pathologies and explore its therapeutic potential for atheroprotection. Methods and Results: We studied the effects of Hdac9 on features of plaque vulnerability using bone marrow reconstitution experiments and pharmacological targeting with a small molecule inhibitor in hyperlipidemic mice. We further used 2-photon and intravital microscopy to study endothelial activation and leukocyte-endothelial interactions. We show that hematopoietic Hdac9 deficiency reduces lesional macrophage content while increasing fibrous cap thickness thus conferring plaque stability. We demonstrate that HDAC9 binds to IKK (inhibitory kappa B kinase)-α and β, resulting in their deacetylation and subsequent activation, which drives inflammatory responses in both macrophages and endothelial cells. Pharmacological inhibition of HDAC9 with the class IIa HDAC inhibitor TMP195 attenuates lesion formation by reducing endothelial activation and leukocyte recruitment along with limiting proinflammatory responses in macrophages. Transcriptional profiling using RNA sequencing revealed that TMP195 downregulates key inflammatory pathways consistent with inhibitory effects on IKKβ. TMP195 mitigates the progression of established lesions and inhibits the infiltration of inflammatory cells. Moreover, TMP195 diminishes features of plaque vulnerability and thereby enhances plaque stability in advanced lesions. Ex vivo treatment of monocytes from patients with established atherosclerosis reduced the production of inflammatory cytokines including IL (interleukin)-1β and IL-6. Conclusions: Our findings identify HDAC9 as a regulator of atherosclerotic plaque stability and IKK activation thus providing a mechanistic explanation for the prominence of HDAC9 as a vascular risk locus in genome-wide association studies. Its therapeutic inhibition may provide a potent lever to alleviate vascular inflammation. Abstract : Supplemental Digital Content is available in the text.